“The Staircase Model” – Labor Control of Temporary Agency Workers in a Swedish Call Center - Olofsdotter, Gunilla (Nordic Journal of Working Life Studies, 2012)
The article explores the labor control practices implemented in a call center with extensive contracting of temporary agency workers (TAWs). More specifically, the article focuses on how structural and ideological power works in this setting and on the effects of this control for TAWs’ working conditions. Open-ended, semi-structured interviews were conducted with TAWs, regular employees, and a manager in a call center specializing in telecommunication services in Sweden. The results show that ideological power is important in adapting the interests of TAWs to correspond with those of temporary work agencies (TWAs) and their client companies, in this case the call center. The results also show how ideological power is mixed with structural control in terms of technological control systems and, most importantly, a systematic categorization of workers in a hierarchical structure according to their value to the call center. By systemically categorizing workers in the staircase model, a structural inequality is produced and reproduced in the call center. The motives for working in the call center are often involuntary and are caused by the shortage of work other than a career in support services. As a consequence, feelings of insecurity and an awareness of the precarious nature of their assignment motivate TAWs to enhance their performance and hopefully take a step up on the staircase. This implies new understandings of work where job insecurity has become a normal part of working life.